THE ROLE AND IMPORTANCE OF ELECTRONIC TEXTBOOKS IN EDUCATING STUDENTS’ ARTISTIC-AESTHETIC TASTE - Xudayberdiyev , Mirolim (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
In our country, in recent years, the digitization of education has been supported at the state policy level, and practical work is being carried out to introduce innovative technologies in art education. In particular, research is being conducted to create digital platforms to develop the artistic and aesthetic taste of students in the field of fine arts, and among these, we have also developed an electronic textbook on Composition, the analysis of which is presented below.